Developing Exposure/Response Models for Anticancer Drug Treatment: Special Considerations. (21st January 2015) - Mould, DR; Walz, A‐C; Lave, T; Gibbs, JP; Frame, B
Abstract : Anticancer agents often have a narrow therapeutic index (TI), requiring precise dosing to ensure sufficient exposure for clinical activity while minimizing toxicity. These agents frequently have complex pharmacology, and combination therapy may cause schedule‐specific effects and interactions. We review anticancer drug development, showing how integration of modeling and simulation throughout development can inform anticancer dose selection, potentially improving the late‐phase success rate. This article has a companion article in Clinical Pharmacology & Therapeutics with practical examples. CPT Pharmacometrics Syst. Pharmacol. (2015) 4, 12–27; doi:10.1002/psp4.16 ; published online 21 January 2015